MOTIVASI PETANI SAMIN DALAM MENANAM KACANG TANAH (Studi Kasus Di Dukuh Tanduran Desa Kemantren Kecamatan Kedungtuban Kabupaten Blora) - Yatno Yatno; Marcellinus Molo; Eny Lestari (AGRITEXTS: Journal of Agricultural Extension, 2003)
Samin society is very appreciated about values of togetherness and unity between them. Its realization has been formed on their lives every day. This phenomenon is shape like cooperation, share work, harmonious, honest, aid and protect each other, doesn't hurt another people. For Samin society, togetherness is more important than competition. They never have a feeling lo compete about throne, property and wealthy. Ecently, however, Samin farmer is beginning to plant a peanut on their farm . Whereas, they usually plant another food and crops plants. According to that fact, this research has purpose to examine what kind of motivation that based to the farmer to plant a peanut and relationship between a both of them. Result of research shows that social economic factors for farmers which influence the decision of farmers to plant peanut is 50 % for half age of middle mature category (45-59 years), level of formal education is 80 % on middle level(< 6 years), level ofincome is low 47,5 % and level of cosmopolite is 70 % on middle level (3-4 time). Level of motivation that based to the decision of farmers is level economic motivation that is 42,5 % on low level and level of affiliate motivation is 27,5 % on high and middle level. From coefficient rs analysis and significant test on 95 % level of believes, relationship between age (JO), level offormal education (X2), level of income (XJ) and level of cosmopolite (X4) with economic motivation (YJ) and affiliate motivation (Y2) is really related. Relationship between economic motivation and affiliate motivation is complementary because rs coefficient is positive.